Kris in a Roma diaspora: New insights on transnational conflict resolution - JUAN F. GAMELLA; VASILE M. MUNTEAN (Romani Studies)
This paper examines the system of conflict resolution maintained by a Roma group that has migrated from the Romanian regions of Transylvania and Banat to over 16 countries in Western Europe and North America. The analysis is based on a long-term collaborative ethnography that enabled the detailed reconstruction of 76 conflicts that occurred between 2001 and 2022. Of these conflicts, 56 were resolved through kris hearings conducted by a tribunal of selected judges or krisoniere. This paper provides an initial analysis of this database, addressing four key aspects of the kris procedures: (1) How does this system work today within diasporic networks that rely heavily on digital technologies for transnational communication? (2) What is the profile of the judges or krisoniere and how do they work within the kris assemblies? (3) What types of conflicts does the system address and how are they linked to the socio-political organization of this diaspora? (4) How are kris resolutions enforced in the absence of political leadership or the coercive power of state institutions? This autonomous justice system, epitomized by the kris hearings, represents a form of embedded legal pluralism and network governance. Consensus within this social field is fostered by the goal of minimizing threat and violence while maintaining connectedness in the face of exclusion and discrimination. This article was published open access under a CC BY-NC-ND licence: https://creativecommons.org/licences/by-nc-nd/4.0.